Doing surveys online - Toepoel, Vera (SAGE, 2016)
By suggesting the pros and cons and do's and dont's for each strategy, as well as covering all recent opportunities and developments in the field, this book helps readers to ensure they are getting the most out of the surveying they are doing online.